IMPROVING STUDENTS READING COMPREHENSION OF NARRATIVE TEXT BY USING STUDENT TEAM ACHIEVEMENT DIVISION - ULFATIN, ANI (English Language Education Study Program, 2021)
The present study is about Improving Students Reading Comprehension of Narrative Text by Student Team Achievement Division (STAD). In this study, Student Team Achievement Division (STAD) is conceptualized as a technique to teach reading. The study conducted at SMP Ashabul Kahfi including forty students as participant. It took place in one semester and it employed an action research design which is aimed to identify the problem faced in the learning process and find out the resolution with intention of improving the quality of the teaching process. Data were gained from classroom observation, documentation, the use of questionnaire and interview. Observation sheet, interview sheet, questionnaires sheet, and field note were several instruments used to complete the data. To meet the purposes, this study employed qualitative and quantitative approach as the method to analyzed data gathered. The qualitative strategy was undertaken trough classroom observation, interview and questionnaires. On the other hand, the quantitative strategy was based on descriptive statistic count to all data gathered in cooperative learning STAD. The re-search findings show that STAD improves the students Reading Comprehension of Narrative Text.